Evaluation of a transbronchial cryoprobe for the ablation of pulmonary nodules: an in vitro pilot study - Dániel Hammer; Lilla Büdi; Ádám Nagy; Rita Varga; Péter Horváth (BMC Pulmonary Medicine, 2023)
Abstract Background Ablation of malignant pulmonary nodules is a novel therapeutic option for patients who cannot undergo surgery. Current transthoracic approaches cause pneumothorax and/or bleeding in a significant number of cases. Objective Our purpose with this study was to evaluate cryoablation under in vitro conditions with a commercially available cryosurgery system. Methods We used ballistic gelatin to model the thermal conduction of lung tissue. The cryoprobe was inserted in the ballistic gelatin with two thermal sensors, they were placed 0.5 cm and 1.0. cm from the probe, respectively, temperature was measured on both sides. We used single-, double- and triple-freeze protocols to see if we could freeze it to -20 °C. Results We achieved − 18.6 ± 3.26 °C on the closer sensor (sensor 1) and − 3.7 ± 4.61 °C on the sensor further away (sensor 2) after 15 min using the single-freeze protocol. Using the dual-freeze protocol, we achieved − 23.2 ± 2,23 °C on sensor 1 and − 16.5 ± 2.82 °C on sensor 2. With the triple-freeze protocol we obtained − 23.5 ± 2.38 °C on sensor 1 and − 19.05 ± 3.22 °C on sensor 2. Conclusion With dual-freeze, values above − 20 °C were achieved using nearer sensor data, but a plateau phase occurred as with continuous freezing. Using triple freeze, we reached − 20 °C at a distance of 0.5 cm from the probe, but not at 1 cm; therefore, we did not expand the diameter of the predicted necrosis zone.